HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PERILAKU PERAWAT DALAM PEMBUANGAN SAMPAH MEDIS DI RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA - Sudiharti, .; Solikhah, . (Universitas Ahmad Dahlan, 2012)
Background: Hospitals in organizing the efforts of health services will result in waste that couldaffect the surrounding environment, so it needs a good waste management efforts. The successof waste management is influenced by the behavior of nurses in performing particular medicalwaste specially. The waste management is good and right by the nurses is basically able todistinguish non-medical and medical waste. Factors knowledge and attitude is one factor in theformation of nurse behavior disposal of medical waste in hospitals. This study aims to determinethe knowledge, attitudes and behavior of nurses, determine the relationship of knowledge todetermine the relationship of behavior and attitudes to the behavior of nurses in medical wastedisposal in PKU Muhammadiyah Hospital of Yogyakarta.Methods: This study was an observational analytic, using cross sectional approach. Theresearch tool was used quesionnaire. The population in this study was nurse as many as 155people and sample as many as 60 people who were on morning shift. Analysis of the data usingunivariate analysis using frequency distributions and bivariate analysis using the Kendall taucorrelation test.Results: There was a relationship between the level of knowledge of the behavior of caregiversin the dump medical waste with coeffisien correlation of 0.373 with a significant value (?) are0.002 which indicates that the value of (?) are smaller than the value of alpha (?). There was alink attitudes with behavior of nurses in the disposal of medical waste with coeffisien correlationis 0.414 with a significant value (?) are 0.000 which indicates that the value of (?) are smallerthan the value of alpha (?).Conclusion: There was a relationship between knowledge of the behavior of nurses in medicalwaste disposal in PKU Muhammadiyah Hospital of Yogyakarta. There was a relationshipbetween attitudes to the behavior of nurses in medical waste disposal in PKU MuhammadiyahHospital of Yogyakarta.Keywords: Knowledge, Attitudes, Behavior, Medical Waste.